2020
DOI: 10.3390/fi12030043
|View full text |Cite
|
Sign up to set email alerts
|

BASN—Learning Steganography with a Binary Attention Mechanism

Abstract: Secret information sharing through image carriers has aroused much research attention in recent years with images’ growing domination on the Internet and mobile applications. The technique of embedding secret information in images without being detected is called image steganography. With the booming trend of convolutional neural networks (CNN), neural-network-automated tasks have been embedded more deeply in our daily lives. However, a series of wrong labeling or bad captioning on the embedded images has left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…They built a novel encoding and decoding algorithm in Matlab that outperforms the old approach in terms of performance evaluation [21]. Wu et al (2020) proposed an improved security of image steganography with the least amount of distortion; these models must keep the feature maps created by task-specific networks independent of any concealed information buried in the carrier. To help alleviate the security issue, this paper incorporates a binary attention method into picture steganography to aid enhance embedding payload capacity, and in the meantime [22].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They built a novel encoding and decoding algorithm in Matlab that outperforms the old approach in terms of performance evaluation [21]. Wu et al (2020) proposed an improved security of image steganography with the least amount of distortion; these models must keep the feature maps created by task-specific networks independent of any concealed information buried in the carrier. To help alleviate the security issue, this paper incorporates a binary attention method into picture steganography to aid enhance embedding payload capacity, and in the meantime [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wu et al (2020) proposed an improved security of image steganography with the least amount of distortion; these models must keep the feature maps created by task-specific networks independent of any concealed information buried in the carrier. To help alleviate the security issue, this paper incorporates a binary attention method into picture steganography to aid enhance embedding payload capacity, and in the meantime [22]. Kumar et al (2020) suggested a steganalytic method based on artificial intelligence that uses deep features extracted from stego pictures using deep CNN techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is one of the most effective approaches to protecting important information by hiding it (data hiding). High-tech steganography summarizes the areas for hiding messages using communication and computer technology, nanotechnology and modern advances in sciences such as biology, chemistry and others (Wu et al, 2020;Koptyra & Ogiela, 2020;Abd-El-Atty et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 11 ] introduced advanced ideas, such as skip connection and feature fusion, and designed a novel two-channel deep hidden network (TDHN). Wu et al [ 12 ] introduced an attention mechanism in steganography to alleviate security issues and increase the load capacity.…”
Section: Introductionmentioning
confidence: 99%